2011
DOI: 10.1016/j.jana.2010.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Decision-Making of HIV-Infected Hispanics and African Americans Participating in Clinical Trials

Abstract: Underrepresentation of HIV-infected Hispanics and African Americans in clinical trials seriously limits our understanding of the benefits and risks of treatment in these populations. This qualitative study examined factors that racial/ethnic minority patients consider when making decisions regarding research participation. Thirty-five HIV-infected Hispanic and African American patients enrolled in clinical research protocols at the National Institutes of Health were recruited to participate in focus groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Recent years have seen an increase in the use of community-based participatory research (CBPR) with Latinos [61], and there has been substantial work done on mental health service utilization [62-64], and inclusion and retention in clinical trials among Latinos [65, 66]. However, the current study is the first to adapt an evidence-based intervention for depression and non-adherence in Latinos living with HIV [67].…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have seen an increase in the use of community-based participatory research (CBPR) with Latinos [61], and there has been substantial work done on mental health service utilization [62-64], and inclusion and retention in clinical trials among Latinos [65, 66]. However, the current study is the first to adapt an evidence-based intervention for depression and non-adherence in Latinos living with HIV [67].…”
Section: Discussionmentioning
confidence: 99%
“…(11), in the Retrovirus Epidemiology Donor Studies (REDS-I/-II), demonstrated repository participation rates were lower among African-Americans and Hispanics than among non-Hispanic Whites. These studies suggested that Hispanics are less likely to participate in clinical trials and biobanking because they have concerns related to sharing of genetic data and lack of credibility and trust in research institutions (12, 23). Among focus groups, similar concerns have been reported among racial and ethnic minorities (24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…These include a lack of information about the research process 4,5 and clear descriptions of research benefits, 5 as well as long-standing mistrust of medical and research establishments, 617 misconceptions about trials, 18,19 concerns about being used as a guinea pig, 16,20 and low perceived risk of HIV infection. 21 Furthermore, community engagement models have demonstrated the need for capacity building in communities for them to fully engage in research, capacity building that includes information sharing 5,12,16,2225 and, according to the World Health Organization, teaching knowledge and skills to enable communities to practice effective health promotion. 26 We used participatory approaches to develop knowledge and skills within the community to support engagement in HIV prevention research.…”
mentioning
confidence: 99%